2019
DOI: 10.1093/nar/gkz619
|View full text |Cite
|
Sign up to set email alerts
|

The human 18S rRNA m6A methyltransferase METTL5 is stabilized by TRMT112

Abstract: N6-methyladenosine (m6A) has recently been found abundantly on messenger RNA and shown to regulate most steps of mRNA metabolism. Several important m6A methyltransferases have been described functionally and structurally, but the enzymes responsible for installing one m6A residue on each subunit of human ribosomes at functionally important sites have eluded identification for over 30 years. Here, we identify METTL5 as the enzyme responsible for 18S rRNA m6A modification and confirm ZCCHC4 as the 28S rRNA modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
370
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(402 citation statements)
references
References 77 publications
18
370
0
Order By: Relevance
“…2A), which was shown to be TRMT12 by Western blotting (Fig. S2A), which is consistent with the previous report (31). Furthermore, untagged, endogenous METTL5 also co-immunoprecipitates (co-IP) TRMT112, and reciprocally, TRMT112 antibodies brought down considerable amount of endogenous METTL5 (Fig.…”
Section: Trmt112 Is a Partner Of Mettl5 And Is Important For Mettl5 Asupporting
confidence: 91%
See 1 more Smart Citation
“…2A), which was shown to be TRMT12 by Western blotting (Fig. S2A), which is consistent with the previous report (31). Furthermore, untagged, endogenous METTL5 also co-immunoprecipitates (co-IP) TRMT112, and reciprocally, TRMT112 antibodies brought down considerable amount of endogenous METTL5 (Fig.…”
Section: Trmt112 Is a Partner Of Mettl5 And Is Important For Mettl5 Asupporting
confidence: 91%
“…2E), consistent with the notion that METTL5-TRMT112 specifically mediates methylation of 18S rRNA. A recent independent study also reported TRMT112 as METTL5 partner, and that the METTL5 catalytic activity in vivo requires TRMT112 (31). Somewhat surprisingly, van Tran et al failed to observe in vitro activity of the METTL5-TRMT112 heterodimer on short RNA oligonucleotides corresponding to the sequences surrounding A1832 in the mature ribosome (31).…”
Section: Trmt112 Is a Partner Of Mettl5 And Is Important For Mettl5 Amentioning
confidence: 99%
“…Whether METTL5 methylates the same residue on the 18S and whether it plays a conserved role in regulating the stress response and translation of cytochrome P450 enzymes remain to be seen. Human METTL5 seems to require binding of the methyltransferase activator TRMT112 to be stabilized (17). However, we found that the worm ortholog of TRMT112, C04H5.1, was dispensable for METL-5 stability and activity.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, two m6A rRNA methyltransferases, Mettl5 and ZCCHC4, were discovered. They are responsible for m6A modification of 18S and 28S rRNA, respectively, which influence on ribosome assembly, translation, and finally cell proliferation [25,26].…”
Section: Introductionmentioning
confidence: 99%